2005
DOI: 10.1038/sj.ijo.0803132
|View full text |Cite
|
Sign up to set email alerts
|

Association of K121Q polymorphism in ENPP1 (PC-1) with BMI in Caucasian and African-American adults

Abstract: Objective: To test for association of the ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) K121Q polymorphism with body mass index (BMI) and diabetes in a large sample of Caucasians and African-Americans by selectively genotyping individuals at the extremes of the phenotypic distribution. Subjects: Subsets comprising the extremes of the BMI distribution (10th-20th and above the 90th BMI percentile for Caucasians and between the 10th-30th and above the 80th percentile for African-Americans) from a gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
3

Year Published

2006
2006
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 22 publications
4
50
3
Order By: Relevance
“…Besides, we did not examine the full three-SNP haplotype, a fact that confines comparisons between the two studies somewhat, since it is possible, as indicated by the French study [29], that more than one variant in ENPP1 modulates the risk of type 2 diabetes and obesity. A few other smaller (of the order of 400 to 1,100 participants) and probably statistically underpowered studies found either no association [19,22,37,42], association of the rare Q allele [26] or association of the common K allele with obesity [38]. The reason for the apparent discrepancies between the studies, including ours, that have evaluated the pathogenic impact of the K121Q variant is far from obvious.…”
Section: Discussioncontrasting
confidence: 60%
See 2 more Smart Citations
“…Besides, we did not examine the full three-SNP haplotype, a fact that confines comparisons between the two studies somewhat, since it is possible, as indicated by the French study [29], that more than one variant in ENPP1 modulates the risk of type 2 diabetes and obesity. A few other smaller (of the order of 400 to 1,100 participants) and probably statistically underpowered studies found either no association [19,22,37,42], association of the rare Q allele [26] or association of the common K allele with obesity [38]. The reason for the apparent discrepancies between the studies, including ours, that have evaluated the pathogenic impact of the K121Q variant is far from obvious.…”
Section: Discussioncontrasting
confidence: 60%
“…Similar results were obtained when adjusting for the effects of age and sex (data not shown). To try to replicate previous findings of an influence of the ENPP1 gene on more extreme forms of obesity [29,38], we compared the K121Q genotypes of the subjects above the 90th percentile of the BMI distribution (n=586, mean±SD BMI, 35.7±3.8 kg/m 2 ) with the genotypes of subjects with BMI between the 10th and 20th percentiles (n=583, mean± SD BMI, 21.9±0.4 kg/m 2 ). No differences in allele frequencies or genotype distributions were found between these groups (p=0.6 for the codominant model; p=0.4 for the dominant model for the Q allele; p=0.6 for the recessive model for the Q allele).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Having established the association between ENPP1 K121Q and hyperglycemia, we explored the interaction between K121Q and BMI because of preliminary evidence that the effect of the Q allele on glycemic traits is mediated by an increase in adiposity (3,5,7,13,30) and suggestions that this variant may also contribute to obesity traits (5,6,(31)(32)(33). Although we observed no association of ENPP1 K121Q with BMI or waist circumference, our interaction analysis supports the observation that a higher BMI strengthens the association of this particular polymorphism with elevated insulin resistance and glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Where we encountered a large source of heterogeneity, we addressed it in a sequential manner: first, due to the large allele frequency differences in K121Q across populations (12% Q allele in HapMap CEU, 93% Q allele in HapMap YRI), we restricted the studies to be included in the final metaanalysis to those performed in the ethnic group with the largest number of samples (self-reported European descent); and second, given the suggestions that ENPP1 plays a role in obesity (15,(31)(32)(33) and that obesity may modulate the effect of ENPP1 K121Q on diabetes risk (15,21,22,32-34), we included BMI as a covariate in meta-regression and adjusted the meta-analysis accordingly. Egger's test was used to address publication bias.…”
Section: Methodsmentioning
confidence: 99%